Vertebral–venous fistula: an unusual cause for ocular symptoms mimicking a carotid cavernous fistula. (8th July 2015) - Felbaum, Daniel; Chidambaram, Swathi; Mason, Robert Bryan; Armonda, Rocco A; Liu, Ai Hsi
Abstract : Vertebral–venous fistulas (VVF), or vertebral–vertebral arteriovenous fistulas, are an uncommon clinical entity. Typically, they present as a result of a direct vascular connection between an extracranial branch of the vertebral artery or its radicular components and the epidural venous plexus. These may manifest with signs and symptoms referable to cervical myelopathy secondary to compression or steal phenomenon. To our knowledge, this is the first case to identify a patient who presented with classic ocular symptoms attributable to a carotid cavernous fistula but secondary to a VVF. We present its treatment and clinical outcome. In addition, we present a brief literature review surrounding this uncommon disease.